Classic Mozart And Murrotal Alquran Therapy Music For Increasing Body Weight In LBW Infants - Nur Jaya; Salih Kadhim (Chakra Brahmanda Lentera Institute, 2022)
Background: Low Birth Weight (LBW) continues to be a significant global health problem. If there is LBW, then there must be an effort to increase the baby's weight. One of them is by giving Mozart classical music therapy. Besides that, you can also use the Qur'an's total therapy. The voice of Al-Qur'an (Murottal) has benefits that can affect health. Objective To find out the differences between Mozart's classical music therapy and Murrotal Qur'an therapy to increase body weight in LBW infants aged 0-28 days. Methods: The design used in the study was quasi-experimental. The population is all infants aged 0-28 days. The sample size is 30 respondents using the Purposive sampling technique. Independent variables of the study are classical Mozart music therapy and Murrotal Qur'an therapy. The dependent variable is the increase in body weight in LBW infants aged 0-28 days. Data was collected using a questionnaire, and then the data were analyzed using the Wilcoxon test with a significance level of α ≤ 0.05. Results: The results showed that respondents had a weighted average of before Mozart's Music Therapy of 2242.0 grams, and after Mozart's Music Therapy of 2431.3 grams, weight Before Koran Murotal Therapy was 2049.3 grams, and after Koran Murotal Therapy of 2496, 0 grams. The results showed that p = 0.023 where H1 was accepted and H0 was rejected, which means that there were differences in Mozart's classical music therapy and Murrotal Alquran therapy for weight gain in LBW infants aged 0-28 days. Conclusion: There are differences in Mozart's classical music therapy and Murrotal Alquran therapy for increasing body weight in LBW infants aged 0-28 days.